Implementation of L-Qibla for Qibla Direction Indicators in Graves - Nurul Izza; Sartika Sartika (Islamic Astronomy Department, Sharia and Law Faculty, 2025)
The issue of determining the Qibla direction in Indonesia is a problem in worship that is rarely considered by Muslims, as they typically follow the established direction without rechecking its accuracy. This is especially true for the Qibla direction of graves, which is seldom addressed by academic experts in astronomy or the general public. However, the majority of scholars agree that aligning the deceased towards the Qibla is mandatory. Many people, however, overlook this issue. This neglect is due to the general lack of knowledge about how to accurately determine the Qibla direction, especially for graves. Therefore, there is a need for tools that can be easily understood by the general public. L-Qibla could serve as an alternative for the public to determine the Qibla direction for graves. This research is qualitative, using data collection techniques such as observation, interviews, and comparison. Data was obtained from measuring graves using several criteria and then tested for accuracy with the Istiwa'aini method. The findings are: 1) Many graves have their Qibla direction deviating by up to 40°. 2) The accuracy test of L-Qibla compared to Istiwa'aini showed a small difference, with an average deviation of 0° 46' 48